Resource management scheme of power fiber to the home network slicing - Weichun GE; Huanhuan LUO; Guiping ZHOU; Yingjie WANG; Xiangyu KONG; Luyao GUAN; Chuang SONG; Min ZHANG; Qing LI (Dianxin kexue)
In order to solve the problems,such as inflexible control and management,the variety of services and complex quality of services,a network slicing resource management scheme based on PFTTH network and corresponding multi-services dynamic resource allocation algorithm based on network-slicing-aware was proposed.Simulation results show that the proposed scheme and algorithm can effectively implement QoS guarantee of different network slicing,significantly increase the network resource utilization.